An exploratory study on the antecedents and consequences of workplace envy - Lee, Sookyung; Chung, MyungHo; Ahn, Jiyoung; Lee, Kihyun (Korean Journal of Industrial and Organizational Psychology, 2015)
The purpose of this study is to investigate two concepts of workplace envy - malicious envy and benign envy- and explore the factors influencing the types of envy. In addition, the study examined how malicious envy and benign envy, respectively, is related to behavioral consequences such as voice behavior, feedback seeking behavior, and social undermining. Using the data of 141 employees in 31 teams from 5 organizations in Korea, we found that three antecedents of workplace envy such as self-efficacy, affect-based trust, and cognition-based trust have positive relationship with benign envy and negative relationship with malicious envy. In addition, benign envy appears to increase voice behavior while malicious envy is related to social undermining behavior. The results imply that these two concepts exist in work settings, and have different behavioral outcomes.